Configuración del estatuto del objeto paidófilo en las tres estructuras psíquicas propuestas por el psicoanálisis (neurosis, psicosis y perversión) (2019)
The central theme of the present investigation is pedophilia, which is why it is intended to describe the way in which the desire for the pedophile object is configured from the three psychic structures, Neurosis, psychosis and perversion. In order to achieve this objective, information will be collect from psychoanalytic theory, to differentiate pedophilia from pederasty, compare the experience of love towards children in pedophilia in the three psychic structures and explore the possible answers of why the perverse act of the pedophile and the pederasty is committed.